OS SALTIMBANCOS DA CIA CAMBALHOTAS: BONECOS, SOMBRAS, MÁSCARAS E A REINVENÇÃO DE UM CLÁSSICO - OLIVEIRA, José Evandy Leite (2025)
The present research aims to identify and analyze the multiple techniques linked to animation theater, used for the construction and assembly of the show Os Saltimbancos, performed by Companhia Cambalhotas between 2013 and 2019, and how such techniques act in theatrical production and in the interpretation and animation work of actors at the Teatro de Formas Animadas. The investigation will take place through oral historical research, interviews and bibliographical research on the Teatro de Formas Animadas, exploring names such as Ana Maria Amaral, Valmor Nine Beltrame, Paulo Balardini, among others, contributing in this way for a thought about training in theater, mainly in theater of animated forms, designed and performed on the outskirts of the city of São Luís.